Advancing EFSA's regulatory science: Updated research and innovation needs - European Food Safety Authority (EFSA); Stef Bronzwaer; Yann Devos; Jean‐Lou C. M. Dorne; Bruno Dujardin; Antonio Fernández Dumont; Beatriz Guerra; Claudia Heppner; Estefanía Noriega Fernández; Konstantinos Paraskevopoulos; Carlos G. dasNeves (EFSA Journal)
Abstract This editorial provides an update on research & innovation (R&I) needs that can support EFSA's regulatory science in the coming years. The paper presents research needs for EFSA's work in a number of domains: omics technologies; gut microbiome; new approach methodologies (NAMs); allergenicity risk assessment; aggregate exposure assessment and environmental risk assessment (ERA). In briefly describing R&I needs, the document also addresses emerging challenges and opportunities. The authors acknowledge that this overview is not exhaustive and refer to earlier publications for additional R&I needs, as well as to the roadmaps for a more in‐depth presentation. Finally, the document calls for transdisciplinary research, reflecting on the interdependencies between human, animal, plant and environmental health. This editorial will be valuable to stakeholders, research agenda setters and funders, both public and private, in formulating calls for research and project funding related to food safety.